Political fallout : nuclear weapons testing and the making of a global environmental crisis - Higuchi, Toshihiro (Stanford University Press, 2020)
Political Fallout' is the story of one of the first human-driven, truly global environmental crises-radioactive fallout from nuclear weapons testing during the Cold War-and the international response.